2011
DOI: 10.1248/jhs.57.458
|View full text |Cite
|
Sign up to set email alerts
|

SEp22, Salmonella Dps, a Key Molecule Bearing Both Pathogenicity and Resistance to Environmental Stresses in Salmonella

Abstract: We isolated and characterized a pathogenicity-related protein in Salmonella Enteritidis (SE) from poultry farms, and designated it as SEp22, which was identified later as Salmonella Dps, a DNA-binding protein from starved cells. Expression of SEp22 was regulated by bacterial growth in Luria-Bertani (LB) medium, showing reduced expression in the logarithmic phase but increased expression from the late logarithmic to stationary phases, which was linked to the expression of σ S both in protein as well as mRNA lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…In consideration of the strong infectivity of Salmonella , a better understanding and appropriate risk management of environmental Salmonella are necessary to control the spread of Salmonella to foods in general. Contamination of Salmonella from the environment to food is an important matter for food safety; however, Salmonella is known to persist and survive in the environment even after exposure to such sanitizers as hydrogen peroxide (H 2 O 2 ) ( 1 ), a widely used sanitizing agent.…”
mentioning
confidence: 99%
“…In consideration of the strong infectivity of Salmonella , a better understanding and appropriate risk management of environmental Salmonella are necessary to control the spread of Salmonella to foods in general. Contamination of Salmonella from the environment to food is an important matter for food safety; however, Salmonella is known to persist and survive in the environment even after exposure to such sanitizers as hydrogen peroxide (H 2 O 2 ) ( 1 ), a widely used sanitizing agent.…”
mentioning
confidence: 99%
“…Using diagonal gel analysis, we showed that external PSPS played an important role in the ability of the macrophage-infecting bacteria to moderate oxidative damage in membrane-bound proteins with the attenuation of extracellular SODs. This mechanism is intimately linked to the defense mechanism of S. Typhimurium against phagocytosis (32). It is likely that the overexpression of MdsABC during infection of macrophages also alters the relative abundance of membrane efflux proteins which cooperate in the export of a variety of antimicrobial agents and host antimicrobial peptides (19,33,34,35).…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that SEp22, [11][12][13][14] which is a novel pathogenicity-related factor of S. Enteritidis, and is identical to Salmonella Dps, 15) plays a very important role in the acquisition of the dry-resistance of S. Enteritidis. 16) In the course of studying the characteristics of SEp22, we happened to find that the prolonged batch culturing of SE cells in M9 minimal medium containing 0.8% glucose (a concentration twice higher than that used in the standard culture) significantly reduced their culturability.…”
mentioning
confidence: 99%